All that glitters is not gold: How motives for open innovation collaboration with startups diverge from action in corporate accelerators - Sandra-Luisa Moschner; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2017)
Prior research has shown that investing into startups through corporate venturing is a sufficient tool for inter-organizational learning, harvesting innovation and engaging in entrepreneurial activities. Recently, a new model of open innovation collaboration between incumbents and startups has gained popularity in practice. In corporate accelerator programs both partners collaborate to advance entrepreneurial products by leveraging their complementary resource bases. In our study we, firstly, analyze the underlying external and internal motives that impel established firms to initiate a corporate accelerator and, secondly, which personnel is responsible for this. Further, we examine the adoption of the corporate accelerator practice for collaborating with new firms. In order to shed light onto the phenomenon, we use interview data from ten corporate accelerators (30 interviews with program managers, corporate employees and startups) from various industries in Germany. By drawing on institutional theory our findings show that the diffusion of the open innovation collaboration practice is either imitatively or normatively driven, depending on the position of the initiator. Further, we demonstrate, that incumbents adopt a corporate accelerator program for sourcing external exploitative or explorative knowledge. However, the degree of adoption of the practice is low and, thereby, not internalized. Although the corporate accelerator has still a short history and many programs follow a trial-and-error approach regarding program structures, established firms seem not to be interested primarily in promoting the collaborative usage of complementary assets with startups. It resembles a rather symbolic action utilizing open innovation collaboration as a marketing tool to let the incumbent's innovation activity glitter more. Therefore, we conclude that established firms seem to practice entrepreneurial washing with corporate accelerators similarly to green-washing activities in the field of corporate social responsibility.
Keywords: 330; corporate accelerator; open innovation collaboration; incumbent; startups; complementary resources; degree of adoption; symbolic action